Keeping watch on glucose. - Tamada, J.A.
New monitors help fight the long-term complications of diabetes. While a great many innovative technologies have been proposed, only a fraction are in advanced stages of development. They fall into three categories: implantable monitors, transdermal (through the skin) meters, and meters depending on spectroscopic methods. Each is a far cry from the painful methods used over the last several decades. By offering greater convenience and less pain, the devices encourage people to test more frequently, the extra testing providing previously unobtainable information on trends in glucose levels in response to insulin dosage and other treatments. Also, monitors that provide frequent, automatic readings can be equipped with preset alarms to warn the user of high or low glucose levels. Parents of children with diabetes, for example, can be warned of overnight low glucose, rather than having to wake up each night to check their child's blood sugar. These advances will lead to better decisions about treatment and ultimately reduce the long-term medical complications of diabetes
Keywords: NIR radiation; Automatic readings; Blood sugar; Children; Diabetes long-term complications; Enzymatic electrochemical sensor; Glucose monitors; Glucose oxidase; Implantable monitors; Insulin delivery system; Micropores; Overnight low glucose; Passive diffusion; Spectroscopic methods; Transdermal meters